MONITORING OF Eschericia. coli O157 FROM RAW COWâS MILK IN THE STORAGE TANK IN SLEMAN DISTRICT, YOGYAKARTA - Tri Yahya Budiarso, Marcella Indah Kristanti, (Proceeding of International Congress, 2014)
Escherichia coli O157 is a member of Enterobacteriaceae which has somatic antigen O157. E. coli O157 isassociated with life threatening diseases such as hemorrhagic colitis (HC), hemolytic uremic syndrome(HUS) and thrombotic thrombocytopenic purpura (TTP). Raw milk is considered a high risk food as it ishighly nutritious and serves as an ideal medium for bacterial growth. The aim of this study was to monitorE. coli O157 contamination in the storage tank before distribution in Sleman district, Yogyakarta. Totalof 30 raw milk samples were collected from the storage tank in Sleman district. Tryptic Soy Broth (TSB)media added with novobiocin was used as enrichment medium, while Chromocult Coliform Agar (CCA)and Chromagar O157 medium for screening test. Additional analysis including serologic and moleculartest of isolates obtained. Based on the screening result, 11,428 colonies were considered as E. coli O157 suspectthat produced red colour in CCA medium. Further screening employing Chromagar O157 mediumresulted in 3 potential colonies which produce mauve colour. These colonies were later tested with LatexTest O157 for serological reason, showing that none were E. coli O157. Molecular analysis with primer pairsfor detection of Stx1 and Stx2 genes confirm that none of the suspected strains have genes that encodedthe toxin, Stx1 and Stx2. These results showed that the presence of STEC (Shiga toxin E. coli) hasnât foundin the tested samples of raw cowâs milk.Keywords: E. coli O157, raw cowâs milk, storage tank, PCR